2005
DOI: 10.1073/pnas.0501559102
|View full text |Cite
|
Sign up to set email alerts
|

Decline in skeletal muscle mitochondrial function with aging in humans

Abstract: Cumulative mtDNA damage occurs in aging animals, and mtDNA mutations are reported to accelerate aging in mice. We determined whether aging results in increased DNA oxidative damage and reduced mtDNA abundance and mitochondrial function in skeletal muscle of human subjects. Studies performed in 146 healthy men and women aged 18 -89 yr demonstrated that mtDNA and mRNA abundance and mitochondrial ATP production all declined with advancing age. Abundance of mtDNA was positively related to mitochondrial ATP product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

56
941
7
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,074 publications
(1,039 citation statements)
references
References 41 publications
56
941
7
10
Order By: Relevance
“…However, the participants evaluated by Fleischman and collaborators were children (8–17 years) and middle‐aged adults (18–55 years) (Fleischman et al ., 2010); the relationship between mitochondrial function and muscle strength may be different in prepubescent children, and in this population, the degree of age‐related mitochondrial impairment may also be small and unlikely to critically affect muscle contraction. This is consistent with the decline in aerobic fitness being relatively modest in young and middle age, likely due to a relative stability of mitochondrial volume and function (Short et al ., 2005; Peterson et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the participants evaluated by Fleischman and collaborators were children (8–17 years) and middle‐aged adults (18–55 years) (Fleischman et al ., 2010); the relationship between mitochondrial function and muscle strength may be different in prepubescent children, and in this population, the degree of age‐related mitochondrial impairment may also be small and unlikely to critically affect muscle contraction. This is consistent with the decline in aerobic fitness being relatively modest in young and middle age, likely due to a relative stability of mitochondrial volume and function (Short et al ., 2005; Peterson et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in animal models and in humans have shown that skeletal muscle mitochondrial oxidative capacity declines with age (Conley et al ., 2000; Short et al ., 2005; Fleischman et al ., 2010; Peterson et al ., 2012), likely due to a decline in both total mitochondrial mass and decreased intrinsic mitochondrial functional capacity (Conley et al ., 2000). This steady decline of mitochondrial function with aging is believed to contribute to the progressive deterioration of muscle strength and quality (Metter et al ., 1999), as diminished energy production may constrain muscle performance, and dysfunctional mitochondria create oxidative stress that can damage proteins and mitochondrial DNA (Peterson et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Defective mitophagy also leads to accumulation of dysfunctional mitochondria which produce more proinflammatory signals, termed mitochondrial damage‐associated molecular patterns (Zhang et al ., 2010; Dall'Olio et al ., 2013). Skeletal muscle from older adults has reduced ATP production, maximal bioenergetic capacity, and mitochondrial content compared to younger counterparts (Short et al ., 2005), and cardiac muscle oxidative phosphorylation capacity is reduced in the earliest stages of heart failure in humans (Diamant et al ., 2003; Hepple, 2016). Skeletal muscle oxidative capacity, mitochondrial content, and fusion are abnormal in older patients with HFpEF (Molina et al ., 2016).…”
Section: How Aging Frailty and Hf Interact To Induce Inflammationmentioning
confidence: 99%
“…Therefore, muscle mitochondrial content and function are directly linked to muscle performance, metabolic disease risk, and quality of life (Conley et al ., 2000; Short et al ., 2005). Both in vivo and ex vivo approaches indicate that skeletal muscle mitochondrial function declines with age in both rodents and humans (Conley et al ., 2000; Amara et al ., 2007; Siegel et al ., 2012; Gouspillou et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%